Harnessing sound waves and vibrations to produce electricity that would power phone chargers inside the LRT 2 and MRT 3 trains - Mendoza, Paolo Lorenzo V.
Sound waves and vibrations can be found everywhere and is produced by almost everything. With the right amount, we could harvest them through piezoelectric transducers and produce electricity. This type of technology could be applied here in the Philippines by setting them up on the MRT 3 and LRT 2 trains. The limited electricity produced could then be used to power phone chargers to help ease our daily lives' reliance on electronics.